Bài 43 Trang 176 SGK Đại số và Giải tích 12 Nâng cao

Tìm nguyên hàm của các hàm số sau

Lựa chọn câu để xem lời giải nhanh hơn

LG a

\(y = x{e^{ - x}}\); 

Giải chi tiết:

Đặt

\(\left\{ \matrix{
u = x \hfill \cr 
dv = {e^{ - x}}dx \hfill \cr} \right. \Rightarrow \left\{ \matrix{
du = dx \hfill \cr 
v = - {e^{ - x}} \hfill \cr} \right.\)

Suy ra \(\int {x{e^{ - x}}dx =  - x{e^{ - x}} + \int {{e^{ - x}}dx =  - x{e^{ - x}} - {e^{ - x}} + C =  - {e^{ - x}}\left( {x + 1} \right) + C} } \)

LG b

 \(y = {{\ln x} \over x}\).

Giải chi tiết:

Đặt \(u = \ln x \Rightarrow du = {{dx} \over x}\)

Do đó \(\int {{{\ln x} \over x}} dx = \int {udu = {{{u^2}} \over 2}}  + C = {{{{(\ln x)}^2}} \over 2} + C\)

 Nam.Name.Vn

list
close